CONSUMERS INSIGHT : MENJAGA KONSISTENSI KOMUNIKASI BRAND (EVALUASI AKTIVITAS KOMUNIKASI PEMASARAN WAROENG SEMAWIS) - Sri Widowati H, Dyah Pitaloka, Djoko Setyabudi (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
Integrated Marketing Communications should always be considered as an integration communication process to target specific audience in a certain unique way. Therefore it was no longer about how to choose the tools and integrated it all through series of action but to craft the messages, tone, and manner which will be suited the target audiences expectation, need, want, dream, lifestyle. In short, all aspects of life as a human being. Consumers insight, compared to other segmentation criteria (geographic and demographic segmentation) provides more than just numbers and fact, but also in-deptth knowledge about the target audiences and their characteristic as a man. In-depth interviews, focus group discussion and brain storming are some methods that could be used to dig deeper into consumer’s life and portrayed them in detail. Consumers insight built from an understanding of facts or information, which can be seen from the statistic and demographic data, and intuition, which is gained througt in-depth discussion with the target audiences. All data collected from the consumers, which then will called insight, will be use to build a strategic communication patch that could specifically ‘talk’ to the audience and creat a long lasting emotional relationship between brand and the audience.